Arrhythmogenic cardiomyopathy: from preclinical models to genotype-phenotype correlation and pathophysiology - Fan, Xuehui; Yang, Guoqiang; Duru, Firat; Grilli, Maurizio; Akın, Ibrahim; Zhou, Xiao-Bo; Saguner, Ardan M.; El-Battrawy, Ibrahim (Stem cell reviews and reports, 2023)
Arrhythmogenic cardiomyopathy (ACM) is a hereditary myocardial disease characterized by the replacement of the ventricular myocardium with fibrous fatty deposits. ACM is usually inherited in an autosomal dominant pattern with variable penetrance and expressivity, which is mainly related to ventricular tachyarrhythmia and sudden cardiac death (SCD). Importantly, significant progress has been made in determining the genetic background of ACM due to the development of new techniques for genetic analysis. The exact molecular pathomechanism of ACM, however, is not completely clear and the genotype-phenotype correlations have not been fully elucidated, which are useful to predict the prognosis and treatment of ACM patients. Different gene-targeted and transgenic animal models, human-induced pluripotent stem cell-derived cardiomyocyte (hiPSC-CM) models, and heterologous expression systems have been developed. Here, this review aims to summarize preclinical ACM models and platforms promoting our understanding of the pathogenesis of ACM and assess their value in elucidating the ACM genotype-phenotype relationship.